Utilização de veículo aéreo não tripulado na quantificação de áreas de disposição inadequada de resíduos da construção civil - Almeida, Ellen Maria Sampaio (Universidade Federal Rural do Semi-Árido, 2020)
The rapid economic growth and development of the construction industry, in the municipality of Mossoró-RN, meant that there was an increasing generation of waste arising from this activity. The present research has as general objective to propose methodology for the use of unmanned aerial vehicles in the quantification of areas of inadequate disposal of construction waste in the municipality of Mossoró-RN. For this purpose, high resolution satellite images were used for preliminary identification of possible areas for disposal of construction waste. Then, each of these areas was flown over, using the Phantom 4 Advanced drone. The images were processed using computational techniques using the Agisoft Metashape software, for the quantification of construction waste, and thematic maps were elaborated using the free and free QGIS software. Through the proposed methodology, it was possible to generate orthomosaics, in order to obtain the quantification of the area and volume of civil construction waste disposed of inappropriately, proving that unmanned aerial vehicles can assist in the management of this waste. It was verified the existence of 16 areas of irregular disposal of the type of waste studied was verified, being the Rincão district the one that presented the largest accumulated volume of residues, of 19,387.09 m³. In view of the results obtained, the technical feasibility of using unmanned aerial vehicles for the modernization and optimization of control and inspection instruments in areas for the disposal of construction waste is emphasized, which can subsidize the elaboration of public policies.
Keywords: Drones; gerenciamento de resíduos; análise quantitativa.; ENGENHARIAS::ENGENHARIA CIVIL